2020
DOI: 10.1111/acel.13186
|View full text |Cite
|
Sign up to set email alerts
|

Aging aggravated liver ischemia and reperfusion injury by promoting STING‐mediated NLRP3 activation in macrophages

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 41 publications
3
60
0
Order By: Relevance
“…20 During liver ischemia and reperfusion, STING suppression of macrophages inhibited the overactivation of NLRP3 inflammasome and excessive secretion of IL-1β and IL-18, eventually reducing liver injury. 44 However, to our knowledge, there is still lack of explicit data on the role of STING in ALI induced by LPS. In the present study, we discovered that STING deficiency in vivo and in vitro could relieve LPS-induced cellular injury, inflammation, oxidative stress, and pyroptosis in macrophages; however, the beneficial effects from STING deficiency were abolished after NLRP3 overexpression, indicating that the proinflammatory roles of STING relied on the activation of NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…20 During liver ischemia and reperfusion, STING suppression of macrophages inhibited the overactivation of NLRP3 inflammasome and excessive secretion of IL-1β and IL-18, eventually reducing liver injury. 44 However, to our knowledge, there is still lack of explicit data on the role of STING in ALI induced by LPS. In the present study, we discovered that STING deficiency in vivo and in vitro could relieve LPS-induced cellular injury, inflammation, oxidative stress, and pyroptosis in macrophages; however, the beneficial effects from STING deficiency were abolished after NLRP3 overexpression, indicating that the proinflammatory roles of STING relied on the activation of NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…found that activation of bile acids and TGR5 inhibits activation of the NLRP3 inflammasome via the TGR5-cAMP-PKA axis, endogenously constraining NLRP3 inflammasome-related inflammation ( 57 ). Some studies have shown that liver ischemia and reperfusion injury triggers activation of the NLRP3 inflammasome in macrophages by STING signaling ( 58 ). Our data indicated that in a mouse model of NASH with deletion of TGR5, the NLRP3 inflammasome was significantly increased, suggesting that TGR5 attenuated inflammation in NASH by inhibiting activation of NLPR3.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are required. Activation of STING increases liver perfusion injury, but in aged animals subjected to ischemia-reperfusion, it also activates NLRP3 inflammasome to further enhance the tissue inflammation via aggravated IL-1β and IL-18 release along with other pro-inflammatory cytokines (TNF-α and IL-6) ( 130 ). Hence, age also affects STING-mediated inflammatory diseases.…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%